Use of rotational angiography in assessing relationship of the airway to vasculature during cardiac catheterization. Issue 6 (17th August 2015) - Truong, Uyen T.; Fagan, Thomas E.; Deterding, Robin; Ing, Richard J.; Fonseca, Brian M.
Abstract : Objectives: We are the first to describe the use of three‐dimensional rotational angiography (3DRA) in creating multiplanar reconstruction (MPR) and volume rendering, in the catheterization suite, of airways at risk for compression by adjacent cardiac structures. Background: 3DRA has emerged as a promising tool for improved visualization of cardiac and vascular structures in congenital heart disease. Methods: This is a retrospective review of all available cases at our institution in which MPR from 3DRA was used to assess airways in relation to surrounding cardiovascular structures. Results: Eight cases were reviewed from January 1, 2011 to November 30, 2013. Seven children had complex biventricular anatomy, including repaired truncus arteriosus, repaired absent pulmonary valve, repaired double outlet right ventricle, and vascular rings. One child had double inlet left ventricle and had undergone a hybrid procedure (stenting of the patent ductus arteriosus and banding of bilateral pulmonary arteries) before the Glenn procedure. Six of these cases involved distortion or stenosis of the pulmonary conduit or branch pulmonary arteries. In all cases, the trachea and the main bronchi were clearly visualized using MPR. Management was affected by the visualization of the airways during the catheterization procedure in seven of eight cases. Four cases had intraprocedural bronchoscopy that confirmed airway findings seen by MPR. In one case, computed tomography confirmed left bronchial compression seen by MPR. Conclusions: 3DRA can visualize airway anatomy and its relationship to the vasculature accurately. This has significant implications for preinterventional planning, intraprocedural management, as well as postprocedural recovery. © 2015 Wiley Periodicals, Inc.